Reasonable Chastisement of Children: An In-depth Analysis of Legal and Ethical Perspectives - Sukhum, Juntratip; Arnee, Nonglak (Journal of Human and Society, Sisaket Rajabhat University, 2024)
This research article has objectives to study the legal and ethical perspectives, as well as to compare the parental punishment in Thailand and other countries, including Sweden, Scotland, the Philippines, Singapore, Malaysia, and the United States of America. And recommend the appropriate methods of disciplining children that align with the social context of Thailand. By using the qualitative research, which focusing on content analysis of documents and various laws. The research findings reveal that in Thailand, under Section 1567 of the Civil and Commercial Code, which allows for “reasonable” punishment of children, the term “reasonable” lacks clarity and may open the door to excessive violence against children. In Sweden and Scotland, they emphasize prohibiting corporal punishment to protect children's rights and dignity in accordance with international standards. For Singapore and Malaysia, they continue to allow corporal punishment but strive to balance the discipline with children welfare. The United States of America, they have a mixed approach, with some states permitting corporal punishment and others enforcing strict bans. However, when it considers to highest interests of children along with the international standard, ethical point of view, guidelines from foreign countries and the findings of research found out that that corporal punishment could harm a child’s dignity, mental health, and lead to aggression, antisocial behavior, and psychological well-being reduction, this research proposes amending of Thai laws to align with international standards. To protect children from all forms of violence and promote the non-violent parenting methods, which will contribute to the development of more appropriate legal frameworks and practices in Thai society.